Hospital effluent in a low-resistance setting is responsible for dissemination of novel antibiotic resistance genes into the marine environment - Manish P. Victor; Vera Radisic; Didrik H. Grevskott; Nachiket P. Marathe (Ecotoxicology and Environmental Safety)
Norway has low prevalence of resistance in the clinics, the contribution of hospital effluent to the spread of antimicrobial resistance (AMR) in the environment is largely unknown. The aim of our study was to determine the role of hospital sewage in dissemination of AMR by defining resistome of hospital effluent, and influent and treated-effluent from the receiving sewage treatment plant (STP) using culture-based methods and metagenomics. Around 94 % E. coli strains (n = 66) were multidrug-resistant (MDR), while 92.3 % of the Klebsiella spp. strains (n = 55) showed MDR phenotype, with some strains carrying carbapenemases, such as NDM-5 (n = 3) and KPC-3 (n = 3). Identical clones of Klebsiella michiganensis were detected in hospital effluent, influent and STP treated effluent. From approximately 238 Gigabases of sequence data, we assembled 1205 antibiotic resistance genes (ARGs) using fARGene method, of which 349 genes represented novel ARGs (< 90 % amino acid identity against known ARGs). Both known and novel ARGs (n = 54) were shared between hospital effluent and the treated effluent of the receiving STP. We assembled 523 metagenome assembled genomes (MAGs) with several representing novel taxa, of which 138 (26 %) MAGs carried 429 ARGs with > 83 % representing putative novel ARGs. Potential pathogens accounted for 60 % of the detected ARGs. Around 15.4 % MAGs were shared between hospital effluent and STP treated effluent. We demonstrate that hospital effluent in Norway has a high diversity of both known and novel ARGs. We show that hospital effluent contributes to the dissemination of not only clinically relevant pathogens but also known and novel ARGs into the receiving marine environment in Norway.